First evidence of altered microbiota and intestinal damage and their link to absence epilepsy in a genetic animal model, the WAG/Rij rat. (11th January 2021) - Citraro, Rita; Lembo, Francesca; De Caro, Carmen; Tallarico, Martina; Coretti, Lorena; Iannone, Luigi Francesco; Leo, Antonio; Palumbo, Domenico; Cuomo, Mariella; Buommino, Elisabetta; Nesci, Valentina; Marascio, Nadia; et al.
Abstract: Objective: A large number of studies have highlighted the important role of the gut microbiota in the pathophysiology of neurological disorders, suggesting that its manipulation might serve as a treatment strategy. We hypothesized that the gut microbiota participates in absence seizure development and maintenance in the WAG/Rij rat model and tested this hypothesis by evaluating potential gut microbiota and intestinal alterations in the model, as well as measuring the impact of microbiota manipulation using fecal microbiota transplantation (FMT). Methods: Initially, gut microbiota composition and intestinal histology of WAG/Rij rats (a well‐recognized genetic model of absence epilepsy) were studied at 1, 4, and 8 months of age in comparison to nonepileptic Wistar rats. Subsequently, in a second set of experiments, at 6 months of age, untreated Wistar or WAG/Rij rats treated with ethosuximide (ETH) were used as gut microbiota donors for FMT in WAG/Rij rats, and electroencephalographic (EEG) recordings were obtained over 4 weeks. At the end of FMT, stool and gut samples were collected, absence seizures were measured on EEG recordings, and microbiota analysis and histopathological examinations were performed. Results: Gut microbiota analysis showed differences in beta diversity and specific phylotypes at all ages considered and significant variances in the Bacteroidetes/Firmicutes ratio between Wistar and WAG/Rij rats. FMT, from both Wistar and ETH‐treated WAG/Rij donors to WAG/Rij rats, significantly decreased the number and duration of seizures. Histological results indicated that WAG/Rij rats were characterized by intestinal villi disruption and inflammatory infiltrates already at 1 month of age, before seizure occurrence; FMT partially restored intestinal morphology while also significantly modifying gut microbiota and concomitantly reducing absence seizures. Significance: Our results demonstrate for the first time that the gut microbiota is modified and contributes to seizure occurrence in a genetic animal model of absence epilepsy and that its manipulation may be a suitable therapeutic target for absence seizure management.